Impacts of Cascade Reservoirs on Adjacent Climate and Land Use Change in the Upper Yellow River, China - Lisen Chen; Penghui Ma; Yalin Nan; Kui Liu (Applied Sciences)
The Yellow River (YR), China’s second-largest river, is rich in water resources, particularly in its upper reaches, which are characterized by mountainous canyons and considerable hydropower potential. Since the 1950s, 24 reservoirs have been constructed along a 918 km stretch of the upper Yellow River (UYR), creating the highest concentration of cascade reservoirs. This development has had significant ecological impacts on the surrounding environment. This study examines the relationship between reservoir attributes and climate factors to evaluate the environmental effects of reservoirs in the UYR. (1) Following reservoir construction, the average annual temperature and precipitation increased by 3–10%, though seasonal and spatial distributions varied. Temperature increases were most pronounced in winter, while precipitation decreased in some regions during spring and summer, although the overall trend remained positive. (2) The ecosystem experienced significant post-construction changes, including reductions in arable land, grassland, and unused land, while water bodies, construction land, and forests expanded. Consequently, the ecosystem within the reservoir area now accounts for 5.2–12.5% of the total area of the region. (3) Temperature and precipitation were closely linked to reservoir attributes, with storage volume (CAP) and long-term average flow (DIS) significantly affecting precipitation, while surface area (AREA) and normal storage level (FSL) had a greater influence on temperature. In conclusion, the dual impacts of reservoir construction on local climate and land use highlight the complex environmental mechanisms involved, providing valuable insights for future reservoir development and ecological protection in the Yellow River Basin and similar regions.